Rehabilitasi Lahan Pasca Tambang Galian C Dengan Jenis Dipterokarpa - Muhammad Fajri (Jurnal Penelitian Ekosistem Dipterokarpa, 2020)
Post-mining land of type-C mineral has caused problems, because it leaves environmental damage. In order to make the former mining environment better, it is necessary to plant tree species that are in accordance with the characteristics of the post-mining land including dipterocarp species.Post Mining of Class C area has caused problems, because they leave environmental damage. In order to make the former mining environment better, it is necessary to plant tree species that are in accordance with post-mining land characteristics including species of dipterocarpa and non dipterocarpa. Purpose this study was to determine effect of fertilization on growth increment and dipterocarp  live percentage as well as non-dipterocarp species live percentage.Research at KHDTK Labanan Berau, East Kalimantan.Plot area size used in the study is 100m x 100m.Treatments used 1kg manure+0.5kg litter;1kg manure without litter;and without applying manure and litter.Each treatment uses 20 plants, with 2 replications in the form of planting lines.Method used experimental with a completely randomized design with 2 plants species and 3 treatments.Data analysis used ANOVA;tree growth analyzed based on increment of height and diameter.Live plants number using live percentage analysis.ANOVA test results for high increment(P-Value=0.951>α=0.05) and diameter increment(P-Value=0.299>α=0.05);B).Average increment of S. leprosula height is 70.44-83.01cm, D. lanceolataa 62.91-72.08cm);Average increment of S. leprosula diameter 0.67-0.97cm, D. lanceolataa 0.59-0.81cm.Dipterocarpa live percentage, S. leprosula 37.5-57.5%, D. lanceolataa 60-75%, 0%.Fertilization treatment not significantly affect height and diameter increment dipterocarp species. Live percentage dipterocarpa species categorized medium-high and non-dipterocarpa between very low-high.Species S. leprosula, D. Lanceolata, can developed for environment improvement of post- mining land of class C